Effect of a patient‐directed discharge letter on patient understanding of their hospitalisation. Issue 9 (September 2014) - Lin, R.; Gallagher, R.; Spinaze, M.; Najoumian, H.; Dennis, C.; Clifton‐Bligh, R.; Tofler, G.
Abstract Background/Aim Poor patient understanding of their diagnosis and treatment plan can adversely impact clinical outcome following hospital discharge. Discharge summaries are primarily written for the doctor rather than the patient. We determined patient understanding of the reasons for hospitalisation, in‐hospital tests, treatments and post–discharge recommendations, and whether a brief patient‐directed discharge letter (PADDLE) delivered during a brief discussion prior to discharge would improve understanding. Methods A prospective randomised controlled trial was conducted, including 67 hospitalised patients. After a baseline questionnaire, patients were randomised to receive the PADDLE letter or usual care. Those receiving the letter had an immediate follow‐up questionnaire. Patient understanding was compared with a summary letter written by the treating clinician, using a 5‐point Likert scale ranging from none to full understanding. A questionnaire was administered at 3 and 6 months. Results At baseline, patients had almost full understanding (median score 4) of reasons for hospitalisation and treatments. However, despite high self‐appraisal, patients objectively had very little understanding of tests performed and post‐discharge recommendations (median 2). Those receiving the letter had an immediate increase to almost full understanding (median 4) of tests performed (P < 0.001) and to full understanding (median 5) of post‐discharge recommendations. This increase did not persist at 3 or 6 months. Conclusions A simple patient‐directed letter delivered during a brief discussion improves patient understanding of their hospitalisation and post‐discharge recommendations, which is otherwise limited. Further evaluation of this brief and well‐received intervention is indicated, with the goal of improving patient understanding, satisfaction and clinical outcomes.